Material didáctico para el proceso de enseñanza aprendizaje de Física en Bachillerato General Unificado - Tocto Flores, Marco Joel (2024)
Didactic materials contribute to the learning of Physics as they are the mediators between knowledge and motivation of students. The objective of this research was to analyze how didactic material is used in the teaching-learning process of Physics in the Unified General High School. Through a non-experimental, descriptive and mixed approach research, the conceptual categories were based on a bibliographic review to determine the didactic materials most used by teachers in the field exploration. The results showed that teachers frequently use didactic strategies that involve the use of concrete materials, such as everyday objects or homemade experiments; while interactive materials are less used. In conclusion, teachers make use of strategies that include different materials to support their classes; however, they need to be constantly updated about resources to add new ones to their repertoire Keywords: teaching and learning, Physics, teaching materials, meaningful learning, experimentation of phenomena